Communication Disorders as Related Handicaps among Noninstitutionalised School-Age Handicapped Children - Donna J; Rudolph; James M Stewart (Journal of All India Institute of Speech and Hearing, 1970)
The purpose of this study was to determine the prevalence and demography of communicative disorders and related handicaps. The results indicated that 1.1% of the school population had related speech, language and hearing disorders.These  789 children reflected 27.4%  of all communicative  disorders. Speech, language and hearing disorders accounted for 62.2,  35.5,  2.3%, respectively, across all primary handicaps. In terms of specific handicaps learning disabilities' (34.9%)  and  trainable mentally retarded (30.5%) accounted for nearly two- thirds of the primary handicaps having associated communicative disorders The study also revealed that race and sex were confounding variables.  For race it was found that blacks were diagnosed more often than  whites for speech and language ; this finding was reversed for hearing disorders.  For sex the findings depended on both the disorder and the race.  Generally males were seen 1.9 times more often than females.